2019
DOI: 10.3389/fphar.2019.00034
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Tissue Distribution, Metabolism, and Excretion of Naringin in Aged Rats

Abstract: Aging is an inevitable biological process characterized by the loss of functional capacity and associated with changes in all phases of pharmacokinetic processes. Naringin, a dietary flavanone glycoside, has been proved to be beneficial for the treatment of multiple age-associated chronic diseases. To date, the pharmacokinetic processes of naringin in aged individuals are still unknown. Thus, a rapid resolution liquid chromatography tandem triple quadrupole mass spectrometry (RRLC-QQQ-MS/MS) method was establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 52 publications
2
63
1
Order By: Relevance
“…The absolute bioavailability of naringin was 44.1% for rats and 34.4% for dogs, indicating a substantial first-pass effect of naringin in these animals. Moreover, compared with the report in aged rats (Zeng et al, 2019), the pharmacokinetic parameters of females were similarly significantly higher than those of males in rats and humans that was likely due to gender-related differences of CYP (Scandlyn et al, 2008).…”
Section: Pharmacokinetic Characteristics and Species Differencescontrasting
confidence: 64%
See 2 more Smart Citations
“…The absolute bioavailability of naringin was 44.1% for rats and 34.4% for dogs, indicating a substantial first-pass effect of naringin in these animals. Moreover, compared with the report in aged rats (Zeng et al, 2019), the pharmacokinetic parameters of females were similarly significantly higher than those of males in rats and humans that was likely due to gender-related differences of CYP (Scandlyn et al, 2008).…”
Section: Pharmacokinetic Characteristics and Species Differencescontrasting
confidence: 64%
“…In previous naringin excretion studies in rats and dogs, Liu et al reported cumulative excretion percentage of 21% for rats and 60% for dogs in the forms of naringin, naringenin, and 4hydroxyphenylpropionic acid (Liu M. et al, 2012); Zeng et al presented a cumulative excretion percentage of 19% in the forms of naringin and naringenin, and 98% for aged rats in the forms of naringin, naringenin, and 4-hydroxyphenylpropionic acid (Zeng et al, 2019). In our clinical studies, the cumulative excretion percentage of the dose was less than 20% in the forms of naringin and naringenin.…”
Section: Excretion and Species Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Further, we measured serum naringenin concentrations following hydrolysis of the conjugated form; however, the method provides an estimation of serum naringenin concentrations. 15,16,20,26,40 Little is known about tissue uptake and disposition of flavonoid metabolites in humans, which is important for the effects of naringenin on cell and tissue function. 41 In rodent studies, dosing with naringenin or naringin produced inconsistent results.…”
Section: Resultsmentioning
confidence: 99%
“…Although it has been suggested that the naringenin metabolites appearing in circulation are treated by the body as xenobiotics and are removed from the system, analysis of the serum concentrations provides valuable information on the pharmacokinetic profile of naringenin . Further, we measured serum naringenin concentrations following hydrolysis of the conjugated form; however, the method provides an estimation of serum naringenin concentrations …”
Section: Discussionmentioning
confidence: 99%